(untitled) (Journal of actual problems of jurisprudence, 2019)
The article deals with the issues of integration on the example of Europe and Asia (for example, the European Union and the EAEC). The need for regional economic integration is now becoming more apparent than in the XX century. Economic integration – the process of economic cooperation between the countries, taking the form of intergovernmental agreements and coordinated by national or intergovernmental bodies, leading to a convergence of economic mechanisms. Cooperation in the form of integration of groups determined by the same level of economic development and the degree of market maturity integrating countries. With rare exceptions, interstate integration of developing or between developed countries or developing countries, in most cases, having common borders and historical economic relations, the presence of general economic and other problems faced by countries in the development, financing, regulation, economy, political cooperation, and so on.d. Key words: integration, EAEC, the European Union, the Eurasian integration, European integration.